Development of Chemistry Learning Videos in the Industries - Artina Diniaty (International Journal of Chemistry Education Research, 2021)
This study aims to develop chemistry learning videos in the industry and determine the feasibility of the developed learning videos. The development model used was adapted from the 4D development model which was carried out only up to the Develop stage. The research instrument used was the needs analysis instrument and the product feasibility assessment instrument. The needs analysis instrument is used to collect data on the analysis of needs and problems in the learning process in schools while the product feasibility assessment instrument is used to collect the feasibility assessment data for the learning video. The results showed that the chemistry learning videos developed were feasible to be used as a learning resource.